Transduodenal Ampullectomy for Ampullary Adenomas: A Safe and Effective Procedure with Long-term Salutary Outcomes. Issue 2 (February 2014) - Mathur, Abhishek; Paul, Harold; Ross, Sharona; Luberice, Kenneth; Hernandez, Jonathan; Vice, Michelle; Rosemurgy, Alexander S.
With widespread use of endoscopy, ampullary adenomas are more frequently identified, many of which are not amenable to endoscopic resection. Pancreatoduodenctomy is curative for these lesions but carries high morbidity. The purpose of this study was to determine the safety and efficacy of transduodenal ampullectomy for these lesions. Data were collected on 32 patients who underwent transduodenal ampullectomy from 2002 to 2010. The median age of patients was 64 years. Adenomas were found because of abdominal pain in 34 per cent, jaundice in 22 per cent, and incidentally on endoscopic screening in 16 per cent and on computed tomography scan of the abdomen in 9 per cent. All patients had a preoperative diagnosis of premalignant disease; 6 per cent required intraoperative conversion to pancreaticoduodenectomy after frozen section evaluation documented carcinoma. Of ampullectomies, 97 per cent had clear margins. Follow-up was 28 months. Four (13%) patients developed recurrent disease at 4 years, 2 years, 1.5 years, and 4 months; all had clear margins at ampullectomy and underwent subsequent pancreaticoduodenectomy with invasive malignancy in a single patient. After preoperative biopsy documenting premalignant disease, malignancy at ampullectomy is unusual. Recurrence is uncommon but occurs even with clear margins necessitating diligent follow-up; even with diligent follow-up, recurrence can be malignant.